Diethyl Oxalate-based Microgrouts in Calcium Carbonate Systems: Formulation and Application Parameters. Issue 7 (8th August 2020) - Porter, Jennifer Herrick; Pasian, C.; Secco, M.
ABSTRACT: During field development of a microgrout for the stabilization of painted lime plasters detached from a limestone substrate, diethyl oxalate-based formulations out-performed microgrouts based on nanolime, colloidal silica and ammonium oxalate, creating more cohesive and homogenous set materials, with better working properties. However, unlike ammonium oxalate, diethyl oxalate is relatively new to the field of conservation, and therefore requires extensive testing to understand its properties and the products of its reaction in calcium carbonate systems before it can be used in conservation treatments. The current study builds on previous testing, to compare the effect of variations in the formulation of diethyl oxalate-based microgrouts bulked with limestone powder, including the effect of application to dry and damp limestone substrates to understand its reaction mechanism, products and performance.